A cooperação portuguesa em Àfrica: S.Tomé e Príncipe - Pereira, Maria Olinda Alves (Páginas a&b: arquivos e bibliotecas, 2013)
A cooperação portuguesa em Àfrica: S.Tomé e Príncipe (Maria Olinda Alves Pereira)